Native Faith (not) only for Men: Gendering Extreme Right-Wing Slavic Neopaganism in Poland - Filip, Mariusz (University of Pardubice, 2015)
The paper is focusing on the question of gender in extreme right-wing Slavic Neopaganism in Poland. My aim is to explore the position(s) of women within this movement. I investigate the rival views of the male-female relationship – subordination and partnership – by comparing two groups related on ideological and personal level, and yet organized according opposing priciples. The example of Zakon Zadrugi “Północny Wilk” exercising the principle “only for men”, and Zakon Krwi Aryjskiej (with a female section Bogini Wojny) exercising the principle “not only for men”, allow me to follow some changes occurring within Neopagan movement in Poland.
Keywords: gender; men's studies; women's studies; Neopaganism; National Socialism; Native Faith; Zadruga; Poland